A prolonged fast improves overnight substrate oxidation without modulating hepatic glycogen in adults with and without nonalcoholic fatty liver: A randomized crossover trial. Issue 3 (9th February 2023) - Roumans, Kay H. M.; Veelen, Anna; Andriessen, Charlotte; Mevenkamp, Julian; Kornips, Esther; Veeraiah, Pandichelvam; Havekes, Bas; Peters, Harry P. F.; Lindeboom, Lucas; Schrauwen, Patrick; Schrauwen‐Hinderling, Vera B.
Abstract: Objective: Increasing overnight fasting time seems a promising strategy to improve metabolic health in individuals with nonalcoholic fatty liver (NAFL). Mechanisms underlying the beneficial effects of fasting may be related to larger fluctuations in hepatic glycogen and higher fat oxidation. This study investigated whether prolonging an overnight fast depletes hepatic glycogen stores and improves substrate metabolism in individuals with NAFL and healthy lean individuals. Methods: Eleven individuals with NAFL and ten control individuals participated in this randomized crossover trial. After a 9.5‐hour or 16‐hour fast, hepatic glycogen was measured by using carbon‐13 magnetic resonance spectroscopy, and a meal test was performed. Nocturnal substrate oxidation was measured with indirect calorimetry. Results: Extending fasting time led to lower nocturnal carbohydrate oxidation and higher fat oxidation in both groups (intervention × time, p  < 0.005 for carbohydrate and fat oxidation). In both arms, the respiratory exchange ratio measured during the night remained higher in the group with NAFL compared with the control group (population p  < 0.001). No changes were observed in hepatic glycogen depletion with a prolonged overnight fast in the group with NAFL or the control group. Conclusions: These results suggest that acutely prolonging the overnight fast can improve overnight substrate oxidation and that these alterations are not mediated by changes in hepatic glycogen depletion.